THE MEXICAN PATH TO A REFORM OF THE NATIONAL PUBLIC SECURITY SYSTEM: BUDGETARY EFFORT IN THE FEDERAL ENTITIES AND MUNICIPALITIES (2008-2015) (Journal of the Spanish Institute for Strategic Studies, 2018)
Th is paper looks at the complicated situation that mexico has been facingsince the beginning of the national public security system reform processin 2006. Th e decision to reform mexican security institutions hadbeen delayed. when the country decided to face up to this challenge,both organized crime and the structural failings of the security agenciesforced the government to take on a double challenge: to recover ungovernableterritories infi ltrated by organized crime – for which the state willneed to fall back on the armed forces, and to fully restructure the nationalpublic security system. Th is paper shows that the argument thatmexico doesn’t invest enough resources in public security is not in linewith reality, but rather that precisely federal and municipal entities haveinvested the most. Th is argument that is in stark contrast to the scarceresults that are to be seen forces society to take a concerned look at thedestination and use of public resources and highlights the importance ofthe debate on the police «single command» in mexican federal entities.